Exploring the link between gut health, diet, and food allergy - Klimczak, Magdalena; Rymarczyk, Barbara; Gawlik, Radosław (Alergologia Polska - Polish Journal of Allergology, 2024)
Food allergy is a growing problem worldwide and its prevalence has increased in recent decades, particularly in developed countries. This increase affects people of all ages, from infants to adults. Symptoms range from non-specific signs affecting isolated organs to severe, life-threatening anaphylaxis. The etiology of food allergy is multifactorial, involving a complex interplay of genetic, environmental and immunological factors. Recent research has highlighted the potential role of an imbalance in the gut microbiota, known as dysbiosis, in the development of food allergy. The gut microbiota refers to the complex ecosystem of microorganisms, including bacteria, archaea, viruses and fungi, that inhabit the human gastrointestinal tract and play a central role in human health, contributing to a range of physiological functions. Recent research has highlighted the potential role of gut dysbiosis in the development of food allergy, particularly in the context of genetic microbiome studies and metabolomics. Changes in the gut microbiota, whether due to dietary habits, fiber consumption, the hygiene hypothesis, proton pump inhibitors, non-steroidal anti-inflammatory drugs, antibiotic use, supplementation and other factors, can potentially influence the immune response leading to the development and severity of food allergy. However, more research is needed to fully understand this relationship and its implications for the prevention and treatment of food allergy. This review aims to provide a comprehensive overview of the current knowledge on the influence of the microbiota on the development of food allergy and to explore the potential of dietary modification as a therapeutic strategy.